Life table parameters of fig mite, Eotetranychus hirsti (Acari: Tetranychidae) under laboratory conditions - Negar Daneshnia; Mohammad Ali Akrami; Maryam Aleosfoor (Persian Journal of Acarology)
Fig mite, Eotetranychus hirsti Pritchard & Baker, 1955, is one of the major pests of fig trees in Estahban (Fars province, Iran). Life table parameters of E. hirsti were studied at 30±1 °C, 60±10% R.H. and 12:12 h (dark: light) photoperiod in 50 replications. The newly laid eggs were placed on the upward surface of fig leaves that were surrounded with a thinned strip of cotton to inhibit mites escaping from Petri dishes. Daily fertility, preimaginal developmental time and mortality rate were analyzed with age-stage, two sex life table analysis software. The result indicated that the developmental times of egg, larva, protochrysalis, protonymph, deutochrysalis, deutonymph and teliochrysalis were 4.32± 0.097, 1.38± 0.069, 1±0, 1.4± 0.07, 1.06± 0.034, 1.4± 0.07, and 1±0 days, respectively. Maximum adult longevity was 8 and 16 days for male and female mites, respectively. Pre-oviposition period, total pre-oviposition period (counted from birth to adult) were 1.5±0.076 and 13.16± 0.133 days, respectively. The mean generation time, net reproduction rate, the intrinsic rate of natural increase and the finite rate of increase were 18.47+0.15 days, 40.5+2.17 offspring, 0.2004+0.003(d-1), and 1.221+0.004 (d-1), respectively. The two-sex life table analysis gives a comprehensive description of the stage differentiation of, Eotetranychus hirsti.